Advanced Ceramic Materials - Mhadhbi, Mohsen (IntechOpen, 2021)
This book examines exciting advancements in the field of ceramics, including nanotechnology, clean energy, and tribology as well as fundamental concepts like defects and structure. It is a comprehensive discussion on how today's ceramics are processed and used in many of today's critical technologies. It discusses current techniques for synthesizing durable and cost-effective ceramic components with biocompatibility, complexity, and high precision. This book is a comprehensive reference for researchers, engineers, dental clinicians, biologists, academics, and students interested in ceramics.